2019
DOI: 10.1590/s1517-707620190003.0730
|View full text |Cite
|
Sign up to set email alerts
|

Subprodutos do babaçu (Orbignya sp)como novos materiais adsortivos: uma revisão

Abstract: RESUMO O Babaçu (Orbignya sp) é uma planta lignocelulósica, disponível em larga escala no norte-nordeste do Brasil, que vem despontado como uma boa fonte de biomateriais, sendo utilizados em vários estudos como adsorventes. Diante disso, o presente trabalho teve como objetivo realizar um estudo prospectivo do uso de subprodutos do babaçu (endocarpo, mesocarpo, epicarpo e carvão ativado) como um material com excelentes propriedades adsortivas, em potencial, para moléculas inorgânicas e orgânicas.O estudo foi re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…Radiation exposure from building materials is mainly due to the presence of radionuclides in the U and Th series. External exposure may be due to gamma emitters found in the material, while internal exposure may be due to radon and thoron gas (Swift et al 1976;Silva et al 2019). The beneficiation processes of REE-containing minerals can generate large amounts of waste.…”
Section: Environmental Impacts From Th-wastesmentioning
confidence: 99%
“…Radiation exposure from building materials is mainly due to the presence of radionuclides in the U and Th series. External exposure may be due to gamma emitters found in the material, while internal exposure may be due to radon and thoron gas (Swift et al 1976;Silva et al 2019). The beneficiation processes of REE-containing minerals can generate large amounts of waste.…”
Section: Environmental Impacts From Th-wastesmentioning
confidence: 99%
“…da Silva et al . (2019b) reported that there are still many studies to be carried out on the production of activated carbon from BBM since the physicochemical characteristics of this bioproduct can be changed using different process parameters, such as temperature, reaction time, and the insertion of reactive substances.…”
Section: Babassu Coconutmentioning
confidence: 99%
“…al. [47] na adsorção de paracetamol uti-lizando carvão ativado de dendê in natura e funcionalizado em meio ácido, bem como em outros processos [48].…”
Section: Adsorção Em Leito Fixocurva De Rupturaunclassified